Reducing translational science roadblocks to disability research - Karen Bonuck; Ariel Fishman (Journal of Clinical and Translational Science)
Disability is a common and universal human experience. Yet, people with disabilities (PWDs) are in poorer health and have less access to quality healthcare than their non-disabled peers. In fact, the National Institutes of Health’s (NIH) designated PWDs as a health disparities population in 2023. This paper illustrates the application of translational science (TS) principles to overcoming roadblocks to reducing PWDs’ health disparities. Part I provides an overview of health disparities among PWDs and the recent designation – situating both within a TS framework. Part II summarizes literature on specific factors that contribute to PWDs’ exclusion from research, how these factors are reflected in background reports that impelled the designation of PWDs as a disparity population, and how the suggested steps to implement the designation reflect TS principles and its research agenda. Part III describes “Reducing Researcher Roadblocks to Including People with Disabilities in Research (D2/R3),” a TS solution to overcoming PWDs exclusion from research. D2/R3 is our institution’s Clinical and Translational Science Award research project – a mixed-methods study that targets research teams’ knowledge, attitudes, biases, and perceptions that contribution to under representation of persons with developmental disabilities in research.